Repetition Blindness for Natural Images of Objects with Viewpoint Changes - Buffat, Stephane; Plantier, justin; Roumes, Corinne; Lorenceau, Jean (Frontiers in Psychology, 2013)
When stimuli are repeated in a rapid serial visual presentation (RSVP), observers sometimes fail to report the second occurrence of a target. This phenomenon is referred to as “repetition blindness” (RB). We report an RSVP experiment with photographs in which we manipulated object viewpoints between the first and second occurrences of a target (0-, 45-, or 90-degree changes), and spatial frequency content. Natural images were spatially filtered to produce low, medium, or high spatial-frequency stimuli. RB was observed for all filtering conditions. Surprisingly, for full-spectrum images, RB increased significantly as the viewpoint reached 90 degrees. For filtered images, a similar pattern of results was found for all conditions except for medium spatial-frequency stimuli. These findings suggest that object recognition in RSVP are subtended by viewpoint-specific representations for all spatial frequencies except medium ones.